Evidence on the financing of industry and trade: Volume 4: National Enterprise Board, Finance for Industry Limited, Equity Capital for Industry - Wilson, Harold (London : H.M. Stationery Off., 1978)
The reports emanated for her majesty office, in view of the committee functions to examine the financial inflow of various institutions.
"Chairman: the Rt. Hon. Sir Harold Wilson."
Includes bibliographical references.
asm; 15/02/19
Loans
Keywords: Finance; Financial institutions